Crystallization by Amorphous Particle Attachment: On the Evolution of Texture. Issue 37 (1st August 2021) - Schoeppler, Vanessa; Stier, Deborah; Best, Richard J.; Song, Chengyu; Turner, John; Savitzky, Benjamin H.; Ophus, Colin; Marcus, Matthew A.; Zhao, Shiteng; Bustillo, Karen; Zlotnikov, Igor
Abstract: Crystallization by particle attachment (CPA) is a gradual process where each step has its own thermodynamic and kinetic constrains defining a unique pathway of crystal growth. An important example is biomineralization of calcium carbonate through amorphous precursors that are morphed into shapes and textural patterns that cannot be envisioned by the classical monomer‐by‐monomer approach. Here, a mechanistic link between the collective kinetics of mineral deposition and the emergence of crystallographic texture is established. Using the prismatic ultrastructure in bivalve shells as a model, a fundamental leap is made in the ability to analytically describe the evolution of form and texture of biological mineralized tissues and to design the structure and crystallographic properties of synthetic materials formed by CPA. Abstract : Biogenic minerals are shown not only to provide key insight into material morphogenesis during crystallization by amorphous particle attachment but also to teach us fundamental new mechanisms that have a profound effect on textural evolution during non‐classical crystal growth. A link between the emergence of texture and amorphous particle accretion rate is established.